2022
DOI: 10.1039/d2tc02498e
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasensitive turn-on luminescence humidity sensor based on a perovskite/zeolite composite

Abstract: Recently, the detection and quantification of humidity has attracted great interest, but for fluorescence sensing of humidity, it is still a challenge to achieve high-performance. Here, we report an ultrasensitive...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 42 publications
0
16
0
1
Order By: Relevance
“…Stimuli-responsive luminescent materials, with a specific response to external stimuli such as light, 1 pressure, 2 solvent molecules, 3 and heat, 4,5 have attracted extensive research interest and have shown wide application potentials in information storage, [6][7][8] chemical sensing, [9][10][11] and anti-counterfeiting. [12][13][14][15] In particular, thermosensitive materials are praised for their simple heating device requirement, highlighting their applications in thermal imaging, and thermometers.…”
Section: Introductionmentioning
confidence: 99%
“…Stimuli-responsive luminescent materials, with a specific response to external stimuli such as light, 1 pressure, 2 solvent molecules, 3 and heat, 4,5 have attracted extensive research interest and have shown wide application potentials in information storage, [6][7][8] chemical sensing, [9][10][11] and anti-counterfeiting. [12][13][14][15] In particular, thermosensitive materials are praised for their simple heating device requirement, highlighting their applications in thermal imaging, and thermometers.…”
Section: Introductionmentioning
confidence: 99%
“…For each RH range, the sensitivity of detection (S) is defined as S = D% PL loss / D% RH i.e., the slope of the calibration curve. 58 % PL loss evolves in three distinct regimes. It strongly increases in the range of 0-23%, with S = 1.30/% RH.…”
Section: Stability Of Nasbwmentioning
confidence: 99%
“…68,77,78 The mechanism of this transformation is that Cs 4 PbX 6 NCs in nonpolar solvent lose CsX at a nonpolar solvent/water interface owing to good solubility of CsX in water and thus convert into CsPbX 3 NCs. [79][80][81][82][83][84][85] Employing this principle, CsPbBr 3 NWs or NRs can be produced via direct or indirect transformation from Cs 4 PbX 6 NCs. 36,38,41,49,50 Zhang et al first applied this method and prepared ultrathin CsPbBr 3 NWs with a diameter of 2.5 nm and a length of up to 10 mm.…”
Section: Interfacial Chemical Transformationmentioning
confidence: 99%